Pathological Diagnostic Pitfalls in the Verification of Brain Tumors; Can Imaging Lead to Pathology Alternation? - Javadinia, Seyed Alireza; Anvari, Kazem; Bahadorkhan, Gholamreza; Samini, Fariborz; Izadpanahi, Payam; Bayatmokhtari, Narges (Reports of Radiotherapy and Oncology, 2015)
Background: Pathological diagnosis of the brain tumors is very challenging. The current study aimed at evaluating the discordance between imaging data and pathologic diagnosis of patients with brain tumors. Methods: The current descriptive study retrospectively assessed the medical documents of patients referred to neuro-oncology clinics of Omid and Emam Reza hospitals affiliated to Mashhad University of Medical Sciences, Mashhad, Iran from 2009 to 2010. The accordance of pathologic reports with imaging findings was studied and the smears were also reviewed in case of discordance. Result: Imaging/pathologic discordances were found in 11 out of 240 (4.5%) patients, which in 82% of the patients was associated with diagnosis change. Discussion: The current study showed that imaging/pathologic discordances existed and were accompanied by changes in management. Treatment approach and prognosis of patients with brain tumors substantially varies among the different subtypes and grades. Considering the limited sources in the developing countries such as Iran, reviewing the pathological findings of all patients is not practical. Therefore, it is suggested that 3 main diagnostic fields involved in the treatment of brain tumors (ie, neuro-oncology, neurosurgery, and pathology) should be familiar with all corresponding issues.